What the Bible is all about : an easy to understand survey of the Bible - Mears, Henrietta Cornelia, 1890-1963 (Minneapolis, MN : Billy Graham Evangelistic Association, 1966)
Includes maps, charts, etc.
Teacher's volume.
Keywords: Bible. -- introductions